Przedsiębiorczy styl kierowania i jego znaczenie dla rozwoju organizacji - Gruszczyńska-Malec, Grażyna; Rutkowska, Monika (Entrepreneurial management style impact on organization development, 2005)
The dynamic changes which took place in companies' environment in previous century, communication and information technology development, globalization process and resulting competition exacerbation will significantly influence notion of company management for a long time. Contemporary companies function in unpredictable and unstable conditions of economical environment and hence this flexible management and self-adapting to continuously changing conditions became abilities of basic importance. One of the possible ways of adapting to highly turbulent environment is entrepreneurial management style. This paper presents the model of entrepreneurial attributes containing behavioral expression of these attributes. It presents behaviors creating entrepreneurial style on background of traditional management behaviors and analyzes impact of the entrepreneurial style on organization development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 475-483